Evaluation of prognostic factors for late recurrence in clear cell renal carcinoma: an institutional study - Voskuil-Galoş, Diana; Călinici, Tudor; Piciu, Andra; Nemeş, Adina (Frontiers in Oncology, 2024)
Background and objectivesFollowing nephrectomy with curative intent, a subset of patients diagnosed with non-metastatic renal cell carcinoma (nmRCC) will present late recurrences, with metastatic relapses after 5 years from the surgical intervention. The aim of this study is to evaluate the prevalence of late recurrences in Romanian patients with nmRCC that have undergone surgery and to assess the clinicopathological characteristics prognostic for late-relapse RCC.Materials and methodsThis is a single-center, retrospective and observational study that analyzed patients with nmRCC with clear cell histology who underwent surgical resection of the primary tumor with curative intent. The patients included in the study were treated and further surveilled according to a personalized follow-up plan between January 2011 and December 2012 in The Oncology Institute "Prof. Dr. Ion Chiricuţă", Cluj-Napoca, Romania. Study endpoints included median disease-free survival (DFS), median overall survival (OS), as well as evaluation of possible prognostic factors indicative of late relapse.ResultsIn the study cohort (n=51), the median DFS was 46 months and median OS was 130 months. DFS was significantly correlated with the International Metastatic Renal Cell Carcinoma Database Consortium (IMDC) score (p=0.04, HR=2.48; 95% CI [1.02, 6.01]), neutrophil to lymphocyte ratio (NLR) (a higher NLR value was associated with a poorer DFS, p=0.035), tumor size (T4 tumors vs. T1 p<0.05, HR=9,81; 95% CI [2.65, 36.27]) and Fuhrman nuclear grade (Fuhrman grade 1 vs. Fuhrman grade 3 p<0.05, HR=4,16; 95% CI = [1.13,15.22]). Fifty one percent of the patients included experienced disease relapse. From this subgroup, a significant percentage of 42% patients presented disease recurrence after 60 months from nephrectomy. OS was correlated to IMDC score (p=0.049, HR=2.36; 95% CI [1, 5.58]) and Fuhrman nuclear grade (Fuhrman grade 1 vs. Fuhrman grade 3 p<0.05, HR=3,97; 95% CI [1.08, 14.54]).ConclusionsThe results of this study support the previously presented biological behavior of RCC, demonstrating that late recurrences in RCC are not uncommon occurrences and patients with localized RCC should be followed up for a longer interval after the surgery for the primary tumor. In addition, the study strengthens the data supporting certain biomarkers as valuable prognostic factors determining survival outcomes of patients with RCC.